Uncovering Natural Longevity Alleles from Intercrossed Pools of Aging Fission Yeast Cells. Issue 2 (8th February 2018) - Ellis, David A; Mustonen, Ville; Rodríguez-López, María; Rallis, Charalampos; Malecki, Michał; Jeffares, Daniel C; Bähler, Jürg
Abstract: Chronological lifespan of non-dividing yeast cells is a quantitative trait that reflects cellular aging. By monitoring allele frequencies in aging segregant pools, Ellis et al. uncover regulatory variants in the 5'-untranslated regions of two genes... Quantitative traits often show large variation caused by multiple genetic factors . One such trait is the chronological lifespan of non-dividing yeast cells, serving as a model for cellular aging. Screens for genetic factors involved in aging typically assay mutants of protein-coding genes. To identify natural genetic variants contributing to cellular aging, we exploited two strains of the fission yeast, Schizosaccharomyces pombe, that differ in chronological lifespan. We generated segregant pools from these strains and subjected them to advanced intercrossing over multiple generations to break up linkage groups. We chronologically aged the intercrossed segregant pool, followed by genome sequencing at different times to detect genetic variants that became reproducibly enriched as a function of age. A region on Chromosome II showed strong positive selection during aging. Based on expected functions, two candidate variants from this region in the long-lived strain were most promising to be causal: small insertions and deletions in the 5′-untranslated regions of ppk31 and SPBC409.08 . Ppk31 is an ortholog of Rim15, a conserved kinase controlling cell proliferation in response to nutrients, while SPBC409.08 is a predicted spermine transmembrane transporter. Both Rim15 and the spermine-precursor, spermidine, are implicated in aging as they are involved in autophagy-dependent lifespan extension. Single and double allele replacement suggests that both variants, alone or combined, have subtle effects on cellular longevity. Furthermore, deletion mutants of both ppk31 and SPBC409.08 rescued growth defects caused by spermidine. We propose that Ppk31 and SPBC409.08 may function together to modulate lifespan, thus linking Rim15 /Ppk31 with spermidine metabolism.